AS RELAÇÕES DE COOPERAÇÃO INTERORGANIZACIONAL E O DESENVOLVIMENTO DE VANTAGEM COMPETITIVA MEDIANTE A CAPACIDADE ABSORTIVA - RAMOS, VANESSA SOUZA DE (2018)
This study investigates the transfer of knowledge in the context of interorganizational cooperation networks and its relation with the creation of the absorptive capacity and the development of competitive advantage. One of the biggest challenges of organizations is the access to external knowledge, given the inconstancy and the environmental dynamism to reach this resource in a timely manner is essential to the development of the organization. However, access to knowledge is not the only battle to be overcome in this field, even more important than achieving knowledge is knowing how to recognize what is relevant for the organization, and assimilating this fact in order to contribute to its application and better use in the organizational context. Thus, based on the premise that the cooperation networks produce a profitable environment for the transfer of information between organizations, we sought to analyze the relationships of interorganizational cooperation and the development of competitive advantage through the absorptive capacity. For this purpose the use of theories of networks and dynamic capacities in a complementary way using the model proposed by Lane, Koka, and Pathak (2006) to develop the hypothesis of research. The research was carried out in the Local Productive Arrangement (APL) of Information Technology (IT) located in the region of the municipality of Londrina, northern Paraná State, through a survey in which were identified 127 valid questionnaires, sensed the tabulated answers and later analyzed from the simple linear relationship test. The research variables were divided into 3 main dimensions according to the appropriate theoretical construct, as well as the hypotheses of the research being: a) interorganizational relationships; b) absorptive capacity; and c) competitive advantage. The absorptive capacity dimension was constructed based on three individual variables that refer to the process of measurement of the absorptive capacity being: a) recognition, b) assimilation, and c) application. In order to meet the central objective of the research, simple linear regression was used, through which the variables forming the absorptive capacity were tested initially, thus testing the hypotheses H1, H2, and H3. Considering the existence of a positive contribution between interorganizational relationships and the capacity of organizations to recognize, assimilate and apply knowledge, it was possible to identify that the interfirm relations explain in 37% the development of absorptive capacity in organizations. Then the tests were applied to the variables absorptive capacity and competitive advantage, a positive and significant result was verified, being verified that the capacity of absorption of knowledge developed in the organizations contributes in 31% to the development of the competitive advantage.